A Methods engineering study on Dada's Garments - Ricafrente, Joanne L.; Romero, Maricelle G.; Simon, Arvi Kristine E.; Sto. Domingo, Cheryl T. (College of Engineering, 1999)
The company chosen for this Methods Engineering Study is DADA's Garments. DADA's is a medium scale garments establishment which started in January 10, 1989. In its 10 years of being a subcontractor, it has specialized in products like jog suits, cycling shorts, and children's shirts. Swimsuits and other children's wear are also included in their product line. After documenting the company's present system, several problem areas have been identified and given attention. One problem pertains to the inefficient layout, which does not facilitate the production process flow and also results in a cluttered workplace. With this, a rearrangement of the components in the facility layout, and the addition of storage racks are advised. Another problem focused on by the group is the inadequacy of forms to facilitate the flow of information. Several designs of forms are presented by the group : (1) the Record of Worker's Daily Output, containing information regarding the number of output and rejects each worker produced; (2) the Job Completion Form, where the job number, description and percentage completion are indicated and monitored on a daily basis; (3) the Monthly Wage Record, a summary of all the workers' output and wage for the month; and (4) the Stock Card, used in monitoring the materials purchases and consumption. But since all the data recording and accounting functions are handled by the general manager, a single journal is recommended instead. The journal, named Manager's Journal, contains data on the workers' output and rejects produced and their corresponding wage. This journal shall be kept and updated by the manager. The insufficient company regulations and policies is the third problem addressed in this study. Additional company rules are generated and suggested to be implemented to achieve a more stable and established organization. An implementation strategy is also prepared to determine the feasibility and applicability of the propositions presented.